Current Trends in Failed Back Surgery Syndrome. A Brief Literature Review, Management Guide and the Romanian Perspective - Horatiu Alexandru MOISA; Dan Aurel NICA; Eugen Cezar POPESCU; Aurel George MOHAN; Gabriel IACOB; Alexandru Vlad CIUREA (Modern Medicine)
Failed back surgery syndrome (FBSS), as described by Follett and Dirks is the least desirable situation for any patient dealing with pain in the lumbar region. Not a syndrome in itself, but rather a syntagm, the term FBSS is generally coined to describe unsuccessful surgical results despite correct surgery. Failed Back Surgery Syndrome is an emerging public health problem throughout the World, which has the unfortunate end-results of generating liability, disability and last but not least, heavy psychological and economical tolls. This paper acts as a brief literature review and tries to summarize available data regarding FBSS epidemiology, prevention and treatment. At the same time, the authors wish to offer neurosurgeons and spine surgeons a relevant starting point on how to handle this emerging public healthcare problem and how to help minimize its impact.